Buenas prácticas para el despliegue seguro del servicio de correo electrónico - Almaguer-Perez, Dairis; Hernández-Yeja, Adrian (Revista Científica, 2021)
Email is currently one of the services most affected by the security problems that proliferate on both the Internet and in local networks or intranet. Specialists in telematic services have the great challenge of providing an email service that guarantees its stability and availability, as well as minimizing the risks of identity theft, unwanted emails, and so-called spam emails. The objective of this research is to carry out an analysis of the main security problems that proliferate in this service and to describe a set of good practices for a secure configuration and deployment of the email service, which, in turn, contributes to reducing the security problems associated with this service and consequently achieving greater user satisfaction.